The Analysis of Syntactical Category in Automotive Advertisement's English Slogans - Putri, Azzahra Ruwanda Attina (English Literature Study Program, 2022)
This study examined the syntactic categories used in English slogans in automotive advertisements. Practically, this study examined the types of syntactic category and how it was used in English slogans in automotive advertisements. By employing a descriptive qualitative method in which the data were analyzed using Carnie’s (2013) theory of syntactic category, the researcher took the data from the official website of several automotive brands. The researcher chose ten English slogans of automotive advertisements from America and Asia consisting of phrases and sentences which became the data of this study. The results of this study revealed that there were two kinds of phrases and sentences, including five noun phrases, one adjective phrase, three imperative sentences, and one interrogative sentence in the automotive commercials. To investigate the word function and position in English slogans, the data were described by using a tree diagram. Furthermore, it could be concluded that the mostly used phrases and sentences in English slogans in automotive advertisements were noun phrases and imperative sentences. Through the results of this study, it is suggested that the next researchers can use other objects of the study besides the automotive commercials from America and Asia. Further studies can also be conducted in English advertising slogans in other products, such as motorcycle, food, cloth, tourism, phone, beauty and other commercials.